2020
DOI: 10.1016/j.bbih.2020.100173
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine storm induced new onset depression in patients with COVID-19. A new look into the association between depression and cytokines -two case reports

Abstract: Background Depression appears to be a common complication in patients during and post–COVID-19 infection. Understanding the mechanism of action of cytokines such as interleukin-6, interleukin-10 and others in depression and in cytokine storm syndrome, the core component of COVID- 19, could shine a new light on future treatment options for both disorders. Objective This review demonstrates the role of interleukins in COVID-19 pathogenesis and their role in depression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 34 publications
1
74
0
5
Order By: Relevance
“…Alpert et al (2020) described two cases of COVID-19 patients with elevated amounts of IL-6 (25 pg/mL and 26.7 pg/mL respectively) who were diagnosed with major depressive disorder (according to the Diagnostic and Statistical Manual of Mental Disorder, 5th Edition (DSM-5)) during COVID 19 infection. Both patients' depressive symptoms subsided about 6 weeks after initiation of anti-depressant pharmacotherapy and normalization of the inflammatory cytokines [192]. The authors concluded that lower cytokine activity ameliorates depressive symptoms as normalization of IL-6 plasma levels decreased depression with or without antidepressants [192].…”
Section: Elevated Levels Of Il-6 In Patients With Covid-19 Infectionmentioning
confidence: 96%
See 4 more Smart Citations
“…Alpert et al (2020) described two cases of COVID-19 patients with elevated amounts of IL-6 (25 pg/mL and 26.7 pg/mL respectively) who were diagnosed with major depressive disorder (according to the Diagnostic and Statistical Manual of Mental Disorder, 5th Edition (DSM-5)) during COVID 19 infection. Both patients' depressive symptoms subsided about 6 weeks after initiation of anti-depressant pharmacotherapy and normalization of the inflammatory cytokines [192]. The authors concluded that lower cytokine activity ameliorates depressive symptoms as normalization of IL-6 plasma levels decreased depression with or without antidepressants [192].…”
Section: Elevated Levels Of Il-6 In Patients With Covid-19 Infectionmentioning
confidence: 96%
“…The world-wide effect of the coronavirus disease 2019 (COVID-19) pandemic is enormous and is not solely limited to the increased mortality and morbidity rates, but also extends into the mental health of the global population [191]. Considerable amount of clinical data is emerging regarding the manifestation of depression in patients during [192][193][194] and post-COVID 19 infection [192][193][194][195]. It is estimated that about 48% of confirmed COVID-19 cases displayed overt psychological symptoms such as depression and often expressed feelings of regret, loneliness, helplessness, and irritation [196].…”
Section: Elevated Levels Of Il-6 In Patients With Covid-19 Infectionmentioning
confidence: 99%
See 3 more Smart Citations